Effect of individual implicit video-based perceptual training program on high-skilled karatekas` decision making - Milazzo, N.; Fournier, J. (Movement & Sport Sciences - Science & Motricité, 2015)
The aim of this article is to determine the effectiveness of a no-feedback video-based perceptual training program to enhance the decision making of high-level karate fighters. The participants completed nine individual perceptive training sessions using temporally occluded video footage. During these sessions, they were asked to mime the action they would have taken in the observed situation as rapidly and as accurately as possible. The results revealed that the participants, who received no-feedback video-based perceptual training, significantly enhanced their decision accuracy and their reaction time during the whole length of the program. Moreover, it appears that accurate decisions are made faster than non-relevant decisions. Findings are discussed from empirical and applied coaching perspectives.